Պետական իշխանության և տեղական ինքնակառավարման փոխհարաբերությունները - Տարոն Մարգարյան (ՀՀ ԳԱԱ հրատ.)
В статье анализируется соотношение органов местного самоуправления и государственной власти в Республике Армении, методы и сферы взаимодействия. Анализируется конституционные нормы, касающиеся органов местного самоуправления и государственной власти. The article analyzes the state and local governments relations and forms of cooperation in the Republic of Armenia. It analyzes the constitutional provisions relating to the local government and public authorities.
Keywords: Political Science; Law; Local government; Municipal government